THE EFFECT OF HUMAN IMMUNODEFICIENCY VIRUS (HIV) AND ANTIRETROVIRAL THERAPY ON THE RISK OF PRE-ECLAMPSIA : A TEN YEARS SYSTEMATIC REVIEW - Nur Arniati, Layli; Wulandari, Erlina; Wulansari, Denta; Surya Saputra, Bryan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Human immunodeficiency virus (HIV) infection affects 25 of the US population, with women being the most likely to receive a diagnosis during their reproductive years. Pregnant HIV-infected women are recommended to start antiretroviral therapy (ART) during pregnancy, regardless of CD4 cell count. Research suggests that HIV infection may reduce the risk of pre-eclampsia (PE). Despite PE being the cause of 42,000 maternal fatalities annually, pregnant women living with HIV are less likely to develop pregnancy hypertensive problems. The aim: This study aims to determine the effect of HIV and antiretroviral therapy on the risk of PE. Methods: This work demonstrated compliance with all standards by means of a comparison with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Consequently, experts were able to guarantee that the study was as current as feasible. Publications released in the years 2014–2024 were considered for this search strategy. To do this, a variety of internet reference sites were used, including ScienceDirect and PubMed. Review articles, previously published works, and partially completed works were all selected not to be considered. Results: When we searched the PubMed database, we found 33 papers, but when we searched ScienceDirect, we found 92 publications. Title screening produced a total of 14 articles for PubMed and 23 articles for ScienceDirect in the search results. Eight papers from PubMed and ten from ScienceDirect made up the total of the papers we compiled. Four reviews, four duplicates, and one with insufficient results were all excluded. Nine studies that satisfied the requirements were finally included. Conclusion: This systematic review found that maternal HIV infection and not using antiretroviral therapy reduced the risk of PE. However, further investigations with more well-designed studies with larger sample sizes are still needed.